Corporate headquarters in the twenty-first century: An organization design perspective - Sven Kunisch; Markus Menz; David Collis (Journal of Organization Design, 2020)
The corporate headquarters (CHQ) of the multi-business enterprise, which emerged as the dominant organizational form for the conduct of business in the twentieth century, has attracted considerable scholarly attention. As the business environment undergoes a fundamental transition in the twenty-first century, we believe that understanding the evolving role of the CHQ from an organization design perspective will offer unique insights into the nature of business activity in the future. The purpose of this article, in keeping with the theme of the Journal of Organization Design Special Collection, is thus to invigorate research into the CHQ. We begin by explicating four canonical questions related to the design of the CHQ. We then survey fundamental changes in the business environment occurring in the twenty-first century, and discuss their potential implications for CHQ design. When suitable here we also refer to the contributions published in our Special Collection. Finally, we put forward recommendations for advancements and new directions for future research to foster a deeper and broader understanding of the topic. We believe that we are on the cusp of a change in the CHQ as radical as that which saw its initial emergence in the late nineteenth/early twentieth century. Exactly what form that change will take remains for practitioners and researchers to inform.
Keywords: 650; Corporate headquarters; Corporate center; Organization design; Theory of the firm; Strategy; International business; Organization theory; Digital age; Sustainability